The SWOT Analysis of Halal Industry in Indonesia: NVIVO Study and Literature Review - Rohmadi Rohmadi; Doni Yusuf Bagaskara; Ulvi Faiqotul Hikmah (Al-Muamalat: Jurnal Ekonomi Syariah, 2024)
This study aims to determine the SWOT analysis of the halal industry in Indonesia using a mix method, namely the NVIVO analysis method and literature review studies. Research samples are news articles from trusted sources and national and international journals. From the study results, it was found that the words halal, industry, Indonesia, and product became the dominant words appearing in the discussion of the halal industry. There are four main topics discussed, namely strengths, weaknesses, opportunities, and challenges of the halal industry. The strongest relationship occurs between the challenges of the halal industry and the strength of the halal industry (0.840396), and the weakest between the opportunities of the halal industry and the challenges of the halal industry (0.542586). The results of the literature review show that the strengths and opportunities outweigh the weaknesses and challenges so that the halal industry in Indonesia is feasible to run. The implication of this study is to provide an overview of the topic of the halal industry and the feasibility of the halal industry in Indonesia. It is expected to be used as a reference for prospective entrepreneurs in the halal industry and related policy stakeholders to maximize the halal industry in Indonesia.